2013
DOI: 10.1186/1475-2859-12-20
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale reconstruction and in silico analysis of Klebsiella oxytoca for 2,3-butanediol production

Abstract: BackgroundKlebsiella oxytoca, a Gram-negative, rod-shaped, and facultative anaerobic bacterium, is one of the most promising 2,3-butanediol (2,3-BD) producers. In order to improve the metabolic performance of K. oxytoca as an efficient biofactory, it is necessary to assess its metabolic characteristics with a system-wide scope, and to optimize the metabolic pathways at a systems level. Provision of the complete genome sequence of K. oxytoca enabled the construction of genome-scale metabolic model of K. oxytoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 41 publications
0
18
0
1
Order By: Relevance
“…These observations suggest four culture behaviors with respect to the fluid dynamic conditions: an initial fermentation zone (100–400 rpm), where an increase in OTR favors BD and acetoin production; an intermediate region, whose border is highly sensitive to OTR (since at 550 rpm the metabolic change is evident in terms of mixed acid route products distribution); a third zone (700–1300 rpm), where the culture maximizes microbial growth, and carbon dioxide is the main by‐product; and a last agitation range (1600–2000 rpm), where the increase in stirring speed continues a decrease in microbial growth rate, in OTR ma x and in CO 2 production. According to these observations it can be suggested that R. terrigena is really sensitive to changes in dissolved oxygen availability, as occurs with other bacterial strains able to produce 2,3‐BD …”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…These observations suggest four culture behaviors with respect to the fluid dynamic conditions: an initial fermentation zone (100–400 rpm), where an increase in OTR favors BD and acetoin production; an intermediate region, whose border is highly sensitive to OTR (since at 550 rpm the metabolic change is evident in terms of mixed acid route products distribution); a third zone (700–1300 rpm), where the culture maximizes microbial growth, and carbon dioxide is the main by‐product; and a last agitation range (1600–2000 rpm), where the increase in stirring speed continues a decrease in microbial growth rate, in OTR ma x and in CO 2 production. According to these observations it can be suggested that R. terrigena is really sensitive to changes in dissolved oxygen availability, as occurs with other bacterial strains able to produce 2,3‐BD …”
Section: Resultsmentioning
confidence: 93%
“…For example, Park et al observed that if the stirrer speed was higher than 350 rpm, the production of 2,3‐BD decreased dramatically while the biomass growth increased in cultures with Klebsiella oxytoca using glucose as sole carbon source. In this work, the biomass profiles overlap from 550 to 750 rpm. Ji et al have proposed a two‐stage agitation speed strategy for enhancing 2,3‐BD final concentration with engineered strains of K. oxytoca , because the production declined from 300 rpm, in favor of biomass growth …”
Section: Resultsmentioning
confidence: 99%
“…Studies have found that this microorganism is involved in the treatment of isoprene, trimethylamine, and nitrogen oxides . Moreover, metabolic reconstruction from genomic analysis has indicated that K. oxytoca can also degrade and use formaldehyde as carbon source or even use methanol if H 2 O 2 is present . Other found microorganisms were Stenotrophomonas sp., Achromobacter sp., Actinomyces sp., Alcaligenes faecalis , Burkholderia cepacia , Burkholderia sp., Enterobacter sp., Lactococcus lactis , Mesorhizobium sp., Methylopila henanense , Pseudomonas sp., Serratia sp., and Stenotrophomonas sp., which might be involved in the consumption of formaldehyde and formate (Table ) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, metabolic reconstruction from genomic analysis has indicated that K. oxytoca can also degrade and use formaldehyde as carbon source or even use methanol if H 2 O 2 is present . Other found microorganisms were Stenotrophomonas sp., Achromobacter sp., Actinomyces sp., Alcaligenes faecalis , Burkholderia cepacia , Burkholderia sp., Enterobacter sp., Lactococcus lactis , Mesorhizobium sp., Methylopila henanense , Pseudomonas sp., Serratia sp., and Stenotrophomonas sp., which might be involved in the consumption of formaldehyde and formate (Table ) . Altogether, the cloning and sequencing results clearly suggested that most of the bacteria, most of the microorganisms, that colonized the biofilters were potentially associated to the consumption of formaldehyde.…”
Section: Discussionmentioning
confidence: 99%
“…In order to enhance the production of 2,3-BD but reduce the formation of byproducts in K. oxytoca, many studies seeking strain improvement and fermentation optimization have been executed [10,11,13,16,23]. Recently, we developed a metabolically engineered K. oxytoca strain, in which ldhA and pflB genes were deleted (K. oxytoca ΔldhA ΔpflB), based on its in silico simulation using a genome-scale metabolic model of K. oxytoca, KoxGSC1457 [22,23]. In the K. oxytoca ΔldhA ΔpflB strain, the overall 2,3-BD yield on glucose increased remarkably (0.45 g/g, 90 % of theoretical maximum yield).…”
Section: Introductionmentioning
confidence: 99%